2004
DOI: 10.1002/dvdy.20155
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and embryonic expression of three zebrafish fringe genes: lunatic fringe, radical fringe, and manic fringe

Abstract: Drosophila fringe and its homologues in vertebrates code for glycosyltransferases that modify Notch, altering the sensitivity of this receptor protein to its ligands Delta and Serrate and, thereby, playing an essential part in the demarcation of tissue boundaries. We describe the isolation and characterization of three zebrafish (Danio rerio) fringe homologues: lunatic fringe (lfng), radical fringe (rfng), and manic fringe (mfng). In addition to the sites previously described (Prince et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…Single WISH was done as described previously (Qiu et al, 2004). For immunohistochemical staining, embryos were anesthetized, dechorinated and fixed in 4% paraformaldehyde (PFA)/phosphate-buffered saline (PBS) at 4°C, unless otherwise stated.…”
Section: Whole-mount Mrna In Situ Hybridization (Wish) and Immunohistmentioning
confidence: 99%
“…Single WISH was done as described previously (Qiu et al, 2004). For immunohistochemical staining, embryos were anesthetized, dechorinated and fixed in 4% paraformaldehyde (PFA)/phosphate-buffered saline (PBS) at 4°C, unless otherwise stated.…”
Section: Whole-mount Mrna In Situ Hybridization (Wish) and Immunohistmentioning
confidence: 99%
“…The segments in the three shades of gray indicate an absence of the relevant loss-of-function data. References: a (Bierkamp and Campos-Ortega, 1993), b (van Eeden et al, 1996, d (Holley et al, 2002), e (Westin and Lardelli, 1997), f , g (Dornseifer et al, 1997), h , i , j , k (Jü lich et al, 2005b), l (Prince et al, 2001), m (Qiu et al, 2004), n (Topczewska et al, 2003), o (Ishitani et al, 2005), p (Jiang et al, 1996), q (Itoh et al, 2003), r , and s (Echeverri and Oates, 2007 There is evidence that Delta can also cell-autonomously inhibit the ability of a cell to receive a Delta signal from an adjacent cell (Bray, 2006). The mouse Deltalike-3, which is required for murine segmentation, appears to specifically function in this inhibitory manner (Ladi et al, 2005).…”
Section: The Notch Pathway and Zebrafish Segmentationmentioning
confidence: 99%
“…By combining pet1 in situ hybridization with the detection of rfng transcripts to identify rhombomeric borders (Qiu et al, 2004), we observed that the first pet1-positive cells were located in r1, close to the MHB (data not shown). Because previous results from our laboratory also suggested that the MHB progenitor pool contributed neurons to the ventral anterior hindbrain (Tallafuss and Bally-Cuif, 2003), we specifically tested for the contribution of this pool to r1-2 serotonergic precursors.…”
Section: Pet1-positive Cells Located In R1-2 Originate From the Midbrmentioning
confidence: 99%
“…The following probes were used: tph2 (previously tphR; Teraoka et al, 2004), tph1 (previously tphD1; Bellipanni et al, 2002), and radical fringe (rfng; Qiu et al, 2004). The RZPD EST clone IMAGp998C2214692Q was used to detect pet1 transcripts.…”
Section: In Situ Hybridization and Immunohistochemistrymentioning
confidence: 99%